One for all - Lainoff, Lillie (Farrar Straus Giroux, 2022)
In seventeenth-century France, Tania de Batz's constant dizziness labels her as weak and an outcast in her town, but she dreams of one day being a great fencer like her father, a former Musketeer. Everything changes when her father is killed, and she is sent to attend the Académie des Mariées in Paris. Like everyone else, Tania believes the academy is a regular finishing school, but she soon discovers it is actually a training ground for elite young French socialites to become Musketeers who protect the Crown and uncover threats against him. She finally feels like she has found a place to belong, but things get complicated when she falls for Étienne, her target in uncovering a potential assassination plot, and Tania must decide where her loyalties truly lie.